VIRTUAL LABORATORY MOLDYNGRID AS A PART OF SCIENTIFIC INFRASTRUCTURE FOR BIOMOLECULAR SIMULATIONS - Salnikov, Andrii; Sliusar, Ievgen; Sudakov, Oleksandr; Savytskyi, Oleksandr; Kornelyuk, Alexander (International Journal of Computing, 2010)
Virtual laboratory MolDynGrid has been established for computational researches in structural biology and bioinformatics, especially for molecular dynamics (MD) simulations of biological macromolecules and their complexes. Biomolecular simulation usually requires a very high processing power and huge storage space for MD trajectories. In this study we describe the development of virtual laboratory infrastructure to run massive MD simulations on a Grid infrastructure in a distributed manner. The aim of MolDynGrid development was to provide an efficient infrastructure for automation of MD job processing in Grid. It will assist researchers to use grid technology without having them to be familiar with highly complicated internals of the Grid. Web-portal of MolDynGrid virtual laboratory has been developed (http://moldyngrid.org), which consists of computational, analytical and educational blocks аnd data base of MD simulations.